Extraction and Purification of Piperine from Black Pepper - Arifianto, Alifiah Nuraini; Fatima. M. C., Putri Ajeng; Fariza. K. W., Syahrani Melanie; Wardani, Eviana Kusuma (Madani: Jurnal Ilmiah Multidisiplin, 2024)
Experiments were carried out on the extraction and purification of piperine from black pepper using the Soxhlet method, with the aim of understanding how liquid-solid extraction works using a Soxhlet extractor, testing the purity of piperine using thin layer chromatography (TLC), and identifying alkaloid class compounds based on qualitative tests. Piperine is an alkaloid compound derived from pepper that has antioxidant and anti-inflammatory properties. Piperine is yellow with needle-shaped crystals that are poorly soluble in water but readily soluble in organic solvents. Piperine can be extracted from black pepper by the soxhletation method, which is a repeated extraction with dichloromethane (DCM) solvent using a 2-circulation process of vapor-liquid changes of the solvent with the help of heating. The piperine extract obtained was then separated from the DCM solvent by evaporation to obtain piperine extract weighing 2.5000 grams with a yield of 8.333% when compared to the initial mass of black pepper of 30 grams. The TLC test with ethanol:water eluent gives RF 0.60, so that the extract can be said to be pure, and qualitative tests with Dragendorff reagent give an orange color, indicating the positive presence of alkaloid compounds in the extract in the form of piperine.